Shunt Surgery Efficacy Is Correlated With Baseline Cerebrum Perfusion in Idiopathic Normal Pressure Hydrocephalus: A 3D Pulsed Arterial-Spin Labeling Study - Huang, Wenjun; Fang, Xuhao; Li, Shihong; Mao, Renling; Ye, Chuntao; Liu, Wei; Lin, Guangwu (Frontiers in Aging Neuroscience, 2022)
This study investigated the relationship between preoperative cerebral blood flow (CBF) in patients with idiopathic normal pressure hydrocephalus (INPH) and preoperative clinical symptoms and changes of clinical symptoms after shunt surgery. Thirty-two diagnosed INPH patients and eighteen age-matched healthy controls (HCs) were recruited in this study. All subjects underwent MRI, including 3D pulsed arterial-spin labeling (PASL) for noninvasive perfusion imaging, and clinical symptom evaluation at baseline, and all INPH patients were reexamined with clinical tests 1 month postoperatively. INPH patients had significantly lower whole-brain CBF than HCs, with the most significant differences in the high convexity, temporal lobe, precuneus and thalamus. At baseline, there was significant correlation between the CBF in the middle frontal gyrus, calcarine, inferior and middle temporal gyrus, thalamus, and posterior cingulate gyrus and poor gait manifestation. After shunting, improvements were negatively correlated with preoperative perfusion in the inferior parietal gyrus, inferior occipital gyrus and middle temporal gyrus. Preoperative CBF in the middle frontal gyrus were positively correlated with the severity of preoperative cognitive impairment, and negatively correlated with the change of postoperative MMSE score. There was a moderate positive correlation between anterior cingulate hypoperfusion and improved postoperative urination. Our study revealed that widely distributed and intercorrelated cortical and subcortical pathways are involved in the development of INPH symptoms, and preoperative CBF may be correlative to short-term shunt outcomes.